2003
DOI: 10.1301/nr.2003.may.s17-s26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycemic Carbohydrates on Short-term Satiety and Food Intake

Abstract: We examine the relationships between glycemic carbohydrate and its effects on short-term satiety and food intake. Both high- and low-glycemic carbohydrates have an impact on satiety, but their effects have different time courses. High-glycemic carbohydrates are associated with a reduction in appetite and food intake in the short term (e.g., one hour), whereas the satiating effects of lower-glycemic carbohydrates appear to be delayed (e.g., 2 to 3 hours). There is no consistent evidence that an increase in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 53 publications
10
98
2
Order By: Relevance
“…Although some studies report no relationship between blood glucose and insulin levels with satiety (Steward et al, 1997;Anderson and Woodend, 2003), others have found significant inverse relationships between satiety and glucose and insulin responses with carbohydrate-rich breakfast cereals (Holt et al, 1992;Holt and Brand-Miller, 1995) and with different GI beverages (Anderson et al, 2002). In this study, we observed differences in glucose and insulin, however, there were no differences in subjective measures of satiety (as assessed by VAS) between the two meals and no correlation between GI and satiety.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Although some studies report no relationship between blood glucose and insulin levels with satiety (Steward et al, 1997;Anderson and Woodend, 2003), others have found significant inverse relationships between satiety and glucose and insulin responses with carbohydrate-rich breakfast cereals (Holt et al, 1992;Holt and Brand-Miller, 1995) and with different GI beverages (Anderson et al, 2002). In this study, we observed differences in glucose and insulin, however, there were no differences in subjective measures of satiety (as assessed by VAS) between the two meals and no correlation between GI and satiety.…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, there was no significant difference in other VAS variables examined after consuming the two different GI meals. Most studies have found that a low-GI meal is more satiating and produces more fullness, less desire to eat and decreased intake (Lavin and Read, 1995;Ludwig et al, 1999;Ludwig, 2000;Ball et al, 2003) but other studies suggest that GI has no relation with satiety or subsequent energy intake (Holt and Brand-Miller, 1995;Anderson and Woodend, 2003;Doucet et al, 2003). However, inconsistency of the results may be due to widely varying energy and macronutrient compositions of the test meal in these studies.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have reported that the consumption of LGI foods reduces hunger and/or promotes satiety relative to consumption of HGI foods in the hours following consumption of the meal (Ludwig et al, 1999;Ball et al, 2003;Warren et al, 2003;Wu et al, 2003). The effect of glycaemic CHO on food intake appears to be related to their effects on blood glucose (Anderson and Woodend, 2003). However, the release of putative satiety peptides, mediated by the intensity and length of interaction of CHO in the gastrointestinal tract appears to be a crucial component of mechanisms initiating and sustaining satiety (Anderson and Woodend, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of glycaemic CHO on food intake appears to be related to their effects on blood glucose (Anderson and Woodend, 2003). However, the release of putative satiety peptides, mediated by the intensity and length of interaction of CHO in the gastrointestinal tract appears to be a crucial component of mechanisms initiating and sustaining satiety (Anderson and Woodend, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…satiating than many other foods, including french fries, when served as 1000 kJ portions. According to a review by Anderson and Woodend (2003), high but not low glycaemic responses are associated with increased satiety and/or reduced food intake in the early postprandial phase (1 h) (Holt et al, 1995;Anderson et al, 2002), whereas the reverse occurs in the later phase after a meal (up to 6 h) (van Amelsvoort and Weststrate, 1992). An inverse relationship between glycaemic response and satiety sensation has also been reported, suggesting that low-GI foods are more satiating (Ludwig, 2000;Roberts, 2000), although it has been pointed out that in some of these studies the control of confounding variables was not adequate (Roberts et al, 2002).…”
Section: Energy-equivalent Meals (Study 1)mentioning
confidence: 99%